Executive Functions in Adult Offspring of Alcohol‐Dependent Probands: Toward a Cognitive Endophenotype?. (14th December 2012) - Gierski, Fabien; Hubsch, Bérengère; Stefaniak, Nicolas; Benzerouk, Farid; Cuervo‐Lombard, Christine; Bera‐Potelle, Céline; Cohen, Renaud; Kahn, Jean‐Pierre; Limosin, Frédéric
Abstract : Background: Executive function (EF) impairment in alcohol dependence (AD) has been related to the toxic effects of alcohol on frontal lobes. However, this impairment could be partially present before the onset of the disease and might constitute a vulnerability factor. Although a considerable body of research has investigated executive functioning among AD patients, much less attention has been directed toward high‐risk individuals. Most studies were carried out among children or adolescents, and very few were conducted in adults. The aim of this study was to examine EF in a group of adult offspring of AD individuals. Methods: One hundred and fifty‐five nonalcoholic adults with (family history positive [FHP]) or without (family history negative [FHN]) family history of AD were included in the study. All participants were screened for past and current psychiatric diagnoses, and alcohol, tobacco, and other substance use. They were compared on self‐rated impulsiveness using the Barratt Impulsiveness Scale‐11 (BIS‐11) and EF using a neuropsychological test battery. Results: Group comparison revealed that FHP participants had significantly higher BIS‐11 scores than the FHN participants, while neuropsychological examination revealed lower EF scores for FHP participants. Hierarchical regression analysis revealed that the number of AD family members was a predictor of EF results, whereas impulsiveness was not. Conclusions: Nonalcoholic adult offspring of AD individuals showed increased impulsiveness and decreased EF, suggesting weakness of 2 distinct neurobehavioral decision systems. Findings support evidence that EF weaknesses may qualify as a suitable endophenotype candidate for AD.